Impact of Improved Sugarcane Production Technologies on Pest Incidence - Saravanakumar, (Indian Journal of Extension Education, 2020)
Sugarcane is an important commercial crop cultivated over 23000 ha in Erode District of Tamil Nadu. Attempts were made to improve the productivity and reduce the pest incidence in sugarcane by adopting improved production technology called Sustainable Sugarcane Initiatives (SSI) practices. The experiments were conducted during kharif 2017 in 5 farmers’ field of Poonthurai block of Erode district. The incidence of early shoot borer and red rot incidence was nil under SSI whereas incidence was noticed in the normal planting system. The cane yield was higher in SSI system with 127.5 t/ha and 108.75 t/ha in the normal planting system. 17.24 per cent yield increase was noticed over conventional system. The cost benefit ratio between the SSI and normal planting system was 2.05 and 1.73, respectively. Considering the above facts, SSI shows the reduction in pest incidence and yield advantages over conventional system of sugarcane cultivation.
Keywords: B:C ratio; Pest incidence; Sustainable sugarcane initiatives; Yield